Cost Effective Implementation of a Doctorate in Clinical Laboratory Science Program. - FYDRYSZEWSKI, NADINE A.; KEOHANE, ELAINE M. (Clinical Laboratory Science)
The establishment of an advanced practice level in clinical laboratory science, the Doctorate in Clinical Laboratory Science (DCLS), has been a goal of the clinical laboratory science (CLS) community for more than 10 years. CLS educators at institutions of higher education are challenged to find the resources needed to provide the high-level and relevant didactic and experiential learning opportunities for medical laboratory scientists (MLS) to enter this new career path. Implementation of a DCLS program was achieved using a three phase approach, first adding a CLS track in an existing MS program, then expanding the breadth and depth of the curriculum into a MS in CLS, and using that strong foundation to complete the ladder to the DCLS level. This model also includes interdepartmental collaboration, interprofesional education (IPE), and faculty, course, and resource sharing. The three phase strategic approach provided the faculty and developmental resources and curricular foundation to implement the DCLS program in a cost-effective manner.